A cost-effective data acquisition instrumentation for measurement of base pressure and wall pressure in suddenly expanded flow through ducts - Sethuraman, Vigneshvaran; Rajendran, Parvathy; Khan, Sher Afghan (Penerbit Akademia Baru, 2019)
Internal flow experimental studies such as sudden expansion in ducts have been reported in the literature. However, the methodology of arriving at the results is not discussed elaborately with the accent on the cost involved and time spent in acquiring the data. This paper explains in detail about the experimental procedure, the methodology of arriving at results and the data analysis. The experimental setup with readily available commercial data acquisition instrumentation for a typical sudden expansion internal flow is presented. It was observed that apart from the cost of hardware fabrication, the cost of instrumentation and measuring devices is also huge. This is apparent especially in fluid flow problems, where there is a need to measure pressures at multiple locations. However, commercially available DAQs have a limited number of channels. Thus, the need for an alternative cost-effective data acquisition system (DAQ) with multiple channels is crucial. Hence, an alternate arrangement of DAQ which is considerably cost-effective and is equally efficient as that of the commercial instrument is proposed. The base pressure and wall pressure results obtained using fabricated DAQ had a variation of ± 1% and ± 1.5% respectively, in comparison to that of commercial DAQ. It is reported that these two arrangements give comparable results with very good accuracy and repeatability of results.